2021
DOI: 10.31117/neuroscirn.v4i3suppl.101
|View full text |Cite
|
Sign up to set email alerts
|

Translation, reliability, and structural validity of the Hospital Anxiety and Depression Scale (HADS) in the general population of Mongolia

Abstract: Various psychological, biological, and social factors make people vulnerable to mental health problems. These precursory factors as mental distress, are not sufficient alone for diagnosing a mental disorder but are recognised as risks to mental health. There has been no screening tool available in Mongolia that is adequately validated for mental health screening and neuropsychiatric functions of the brain. Therefore, we aimed to translate and validate the hospital anxiety and depression scale (HADS) to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Among fourteen items, seven of them are for anxiety (HADS-A subscale), and the remaining seven are for depression (HADS-D subscale). The Mongolian version of HADS demonstrated evidence of good validity and reliability for the general population [ 38 ]. Each item is rated on 4-point scale for a total score between 0 and 21 for each subscale.…”
Section: Methodsmentioning
confidence: 99%
“…Among fourteen items, seven of them are for anxiety (HADS-A subscale), and the remaining seven are for depression (HADS-D subscale). The Mongolian version of HADS demonstrated evidence of good validity and reliability for the general population [ 38 ]. Each item is rated on 4-point scale for a total score between 0 and 21 for each subscale.…”
Section: Methodsmentioning
confidence: 99%
“…The ranges of scores for cases on each subscale are 0-7 or normal, 8-10 or mild disorder, 11-14 or moderate disorder, and 15-21 or severe disorder (Zigmond & Snaith, 1983). The two-factor Mongolian version of the HADS had been validated in the general population (Tumurbaatar et al, 2021b).…”
Section: Hospital Anxiety Depression Scale (Hads)mentioning
confidence: 99%
“…Scores falling within the range of 0–7 are classified as normal, scores between 8 and 10 indicate a mild abnormality, scores ranging from 11 to 14 denote a moderate abnormality, and scores from 15 to 21 represent severe abnormality for each subscale. We determined the psychometric properties of the HADS in the general population in our previous study, which demonstrated that the Mongolian version of HADS has good validity and reliability for assessing anxiety and depression 18 .…”
Section: Methodsmentioning
confidence: 99%
“…It comprises of 14 Likert-scale items that represent two latent domains: anxiety and depression. In a previous study, we translated and evaluated the psychometric properties of the Mongolian version of the HADS in the general population, demonstrating good validity and reliability for assessing mental distress 18 .…”
Section: Introductionmentioning
confidence: 99%